Championship racquetball - Davis, Fran , 1954-; Mannino, Jason , 1975- (Human Kinetics, 2011)
A guide to improving one's racquetball game that discusses serves, returns, specialty shots, court positioning, and other related topics and includes instructions for seventy-six skill-development drills as well as practice, training, and match preparation tips